2017
DOI: 10.4103/jomfp.jomfp_60_17
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of cellular metabolism in cancer cells and its therapeutic prospects

Abstract: Transformation of a normal cell into a cancerous phenotype is essentially backed by genetic mutations that trigger several oncogenic signaling pathways. These signaling pathways rewire the cellular metabolism to meet the bioenergetic and biomass requirement of proliferating cell, which is different from a quiescent cell. Although the change of metabolism in a cancer cell was observed and studied in the mid-20th century, it was not adequate to explain oncogenesis. Now, equipped with a revolution of oncogenes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 99 publications
(116 reference statements)
1
19
0
Order By: Relevance
“…Further support to this notion is provided by studies that reported that mutated p53; a tumor suppressor gene was mostly located in the peripheral columnar cells. 3,17,18 It was reported that BMI-1 inactivates p16INK4A and/or p14ARFp53 tumor suppressor pathways which result in promoting cell proliferation. 19 In the present study, immunoreactivity for BMI-1 among the DC group was detected as scarce faintly stained cells in the basal and parabasal layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further support to this notion is provided by studies that reported that mutated p53; a tumor suppressor gene was mostly located in the peripheral columnar cells. 3,17,18 It was reported that BMI-1 inactivates p16INK4A and/or p14ARFp53 tumor suppressor pathways which result in promoting cell proliferation. 19 In the present study, immunoreactivity for BMI-1 among the DC group was detected as scarce faintly stained cells in the basal and parabasal layers.…”
Section: Discussionmentioning
confidence: 99%
“…Ameloblastoma has an insidious growth pattern as it tends to infiltrate between intact cancellous bone at the periphery of the lesion before bone resorption occurs.2 Due to this insidious growth pattern of Am, it is difficult to predict its clinical course which in turn raised a couple of questions such as; whether cancer stem-like cells are present in Am and if its presence plays a role in aggressiveness and recurrence rate of tumor? 2,3 A dentigerous cyst (DC) is the most common type of developmental odontogenic cyst with an indolent behavior and low recurrence rate. 4,5 These cysts are usually asymptomatic and are detected by routine radiographic examination except in large cases.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22]. OSCC is initiated from epithelium-based stem cells that have acquired genetic alterations, such as activation and amplification of oncogenic genes or mutation in tumor-suppression genes [23,24]. Epithelial-to-mesenchymal transition (EMT) plays a vital role in initiating tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy failure is often associated with clonal expansion of a specific subset of tumour cells. The associated metabolic reprogramming [ 21 , 23 , 24 ], suggests that metabolic biomarkers could provide predictive information about therapy failure. Indeed, several lines of evidence indicate that metabolic flexibility is an important determinant of resistance to cancer therapies [ 25 ].…”
Section: Precision Medicine Applications For Breath Biopsymentioning
confidence: 99%